2021
DOI: 10.3389/fgwh.2021.705262
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth for Addressing Sexual and Reproductive Health and Rights Needs During the COVID-19 Pandemic and Beyond: A Hybrid Telemedicine-Community Accompaniment Model for Abortion and Contraception Services in Pakistan

Abstract: The COVID-19 pandemic led overburdened health care systems to deprioritize essential sexual and reproductive healthcare, including abortion and contraception care, while accelerating shifts in healthcare delivery to digital technologies. However, in many countries, including Pakistan, inequalities in access to digital technologies remain, presenting an opportunity for interventions that both increase access to deprioritized sexual and reproductive health and rights (SRHR) services and overcome the digital divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 16 publications
(17 reference statements)
2
23
0
Order By: Relevance
“…Similar models that employ non-clinical support for medical abortion exist throughout the world in a diverse range of legal settings, including Pakistan, Argentina, Mexico, Peru, Ireland, Tanzania, Nigeria, and Indonesia. 13 , 15–19 , 28 , 32–35 The value of ASC has become even more pronounced where legal restrictions on abortion proliferate, and as the COVID-19 pandemic led under-staffed, under-resourced health facilities to deprioritise in-clinic abortion services. While full decriminalisation of abortion is essential to ensure access to abortion, as emphasised in the recent WHO abortion guidelines, 14 decriminalisation may take some time to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…Similar models that employ non-clinical support for medical abortion exist throughout the world in a diverse range of legal settings, including Pakistan, Argentina, Mexico, Peru, Ireland, Tanzania, Nigeria, and Indonesia. 13 , 15–19 , 28 , 32–35 The value of ASC has become even more pronounced where legal restrictions on abortion proliferate, and as the COVID-19 pandemic led under-staffed, under-resourced health facilities to deprioritise in-clinic abortion services. While full decriminalisation of abortion is essential to ensure access to abortion, as emphasised in the recent WHO abortion guidelines, 14 decriminalisation may take some time to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results arising from this research indicate that some women were not able to have their demand met, as was the case in many countries [ 21 ]. However, the digital gap which might be experienced by the most vulnerable collective groups that were not educated on new technologies or lacked good quality access to the Internet should indeed be considered [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are comparable to the safety of medication abortion provided in clinic, both from prior studies and in a randomized controlled trial comparing telemedicine to in-person medication abortion. 45,49 In a majority of studies evaluating telemedicine for medication abortion, preabortion tests, including ultrasound, hCG, or pelvic examination, were compulsory, 6,9,[13][14][15][43][44][45][46][47]50,51 while in a few, ultrasound and/or laboratory tests were only required in cases of uncertain gestation or to confirm intrauterine pregnancies among patients who had already undergone clinical assessment. 4,24,36,42,48,52 Aiken et al 24 and Kerestes et al 13 showed comparable efficacy for no-test telemedicine abortion and medication abortion with mandatory preabortion laboratory testing, imaging studies, or physical examination, whereas Anger et al 52 found higher rates of incomplete abortion in the no-test group versus testing group (risk difference 4.0%).…”
Section: Effectiveness Of Telemedicine Abortionmentioning
confidence: 99%